Exploring the use of in vitro colorimetric and bioluminescence assays to distinguish between Arf GTPase isoforms and detect Arf GTPase activity - Woolf, Alexander Robert (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
ADP-ribosylation factors (Arfs), part of the Ras superfamily of small GTPases, are involved in various key cellular processes such as the regulation of membrane trafficking and organelle structure. Arfs cycle between a GDP-bound 'inactive' conformation and a GTP-bound 'active' conformation, with the latter exerting its functions on various downstream effector proteins. In eukaryotic organisms, Arf6 regulates traffic in the endocytic pathway and contributes the reorganisation of actin cytoskeleton. Due to its ability to affect health and disease in many ways, Arf6 has been a viable drug target for many diseases, with this study focusing mainly on cancer and malaria. In the P. falciparum parasite genome are two genes encoding for Arf GTPase. The first (PfArf1) has been designated as an Arf1 homologue, and the second shares sequence similarities with both human Arf1 and Arf6 but is otherwise uncharacterised. The potential of the second putative malarial Arf sequence to be a homologue of human Arf6 is important as it would further our understanding of the unusual mechanisms behind malarial endocytosis of the red blood cell cytoplasm. To assign this second putative malarial Arf (PfArf6) as a human Arf6 or Arf1 homologue, a novel plate-based colorimetric assay system was used involving the Arf effector binding domains of "golgi-localised gamma adaptin ear-containing ARF-binding protein 3" (GGA3), which interacts with Arf1 and Arf6, and "c-Jun NH2-terminal kinase-interacting protein 4" (JIP4), which interacts with Arf6 only. It was shown that PfArf6 was able to bind to both GGA3 and JIP4 and that PfArf6 was distinguishable from PfArf1. Initial data obtained designated "PfArf6" as an Arf6 homologue, despite the higher sequence similarity between PfArf6 and human Arf1. Arf GTPases display notoriously slow intrinsic GTPase activity and so their activity is tightly regulated by their cognate guanine nucleotide-exchange factors (GEFs) and GTPase-activating proteins (GAPs), which cycle Arfs between their GDP- and GTP-bound conformations. Arf6 and its closely associated regulators are involved extensively in the promotion of tumour growth, invasion, and metastasis stages of cancer. Simple and reproducible GTPase activity assays, that are simultaneously amenable to screening compound libraries for Arf inhibitors, are limited in availability due to the difficulties surrounding accurate GTP detection. A novel in vitro plate-based bioluminescence assay format developed in this study to detect Arf GTPase activity in the presence of its regulators namely "ARF nucleotide-binding site opener" (ARNO) and ArfGAP1. In cells "nucleoside diphosphate kinase" (NDPK) functions to regulate the available nucleoside triphosphate (NTP) pools to maintain homeostasis. Given the relative ease for accurate ATP detection using firefly luciferase and the ability for NDPK the convert GTP to ATP, NDPK and luciferase were utilised in this coupled assay to detect GTP consumption by Arf. Regulator stimulated Arf GTPase activity was eventually detectable to varying degrees for human Arf1 and Arf6, as well as malarial Arf1. Thus, the groundwork for a simple, plate-based assay system has been laid for the detection of the full Arf GTPase activity cycle, the screening of compound libraries for Arf inhibitors, as well as a means of determining Arf GTPase specificity for regulators (and vice versa) in vitro.
Keywords: ADP ribosylation factor; ARF1; ARF6; ARFGAP1; GGA3; NDPK